LENGTH WEIGHT RELATIONSHIP IN THE THREADFIN-BREAM, NEMIPTERUS JAPONICUS ALONG THE KERALA COAST - Vinci, G K; Nair, A K Kesavan (Indian Journal of Fisheries, 2011)
The length-weight relationship in N. japonicus of the Kerala coast showsno change in the form of the relationship when classified according to maturityand sex. The t-test shows that the cubic law does not hold good for thisspecies. Instances of more than one value of weight for a given value of lengthare found more frequently in females than in males. A comparison of the relationshipsfor the Andhra-Orissa coasts with those of the Kerala coast givessome differences which probably signify that separate stocks may exist in theBay of Bengal and the Arabian Sea